PENGARUH VOLUME DAN FREKUENSI PERDAGANGAN TERHADAP HARGA SAHAM PADA BANK INDEX LQ45 - PERIODE 2020 – 2024 - Hartanto, Hartanto (Politeknik Negeri Lhokseumawe, 2024)
Abstract: The purpose of this study is to examine and analyze whether there is an effect of the independent variables, Trading Volume and Frequency Transactions, and the dependent variable, Stock Prices. The research employs a causal research method, conducted on 7 (seven) banks included in the LQ45 Index on the Indonesia Stock Exchange during the period of 2020-2024. The statistical test model used is multiple linear regression. The results of this study indicate that Trading Volume and Frequency Transactions have a significant effect on stock prices. Keywords: Trading Volume, Trading Frequency, LQ45, Bank, Stock Price.